Production of Thin Films with ionic self-assembled supramolecular order using the Dye Congo Red and the Surfactant Benzyldimethyldodecylammoniumchloride (BC12) - Rosenberg, Anders; Hilber, Christoffer; Andersen, Daniel; Matrawy, Sarah (UCPH NanoScience - a student research journal, 2017)
N/A